Introduction Of Intersecting Gilling Machine In Jute Processing For Making Jute And Blended Yarn (Daffodil International University Journal of Science and Technology, 2011)
The study was aim to determine the suitability of intersecting gilling machine in jute processing system. In this regard the machine was used for processing of jute fibre to yarn [1]. The third drawing sliver passed through the intersecting gilling of GN5 type into 4:1 input –output ratio of slivers. Yarns spun by this slivers through different types of spinning frame. Quality ratio of jute yarns produced from different spinning machines were measured. These were for Hessian Spinning machine is 84.17%, Apron draft spinning frame is 88.59% and Spingard spinning frame 96.34%. However for medium count jute-polypropylene blended yarn, the quality ratios are between 102- 112 and yarns were spun by hessian spinning frame. These results compared with the yarn produced through conventional jute spinning system (except intersecting Gilling machine, table 2). Findings of the study indicate a new era for the jute processing by using intersecting Gilling machine. It is observed that the introduction of Intersecting Gilling machine has a potential prospect in jute processing for making fine jute yarn. Keywords: Intersecting gilling; drawing machines; spinning machines; jute yarn. DOI: http://dx.doi.org/10.3329/diujst.v6i2.9347 DIUJST 2011; 6(2): 63-66